Z Zagadnień Technicznej Teorii Nośności Granicznej Płyt o Mieszanych Warunkach Brzegowych - Sawczuk, A.; Janas, M.; Zawidzki, J. (Engineering Transactions, 1962)
Some test results are described concerning the limit load of R.C. plates, The purpose of the tests. was to verify the solutions of the yield line theory for plates with mixed boundary conditions. The tests included the determination of a) the collapse load (compared with theoretical results), b) the collapse made in function of the orthotropy ratio (for prescribed boundary conditions), c) the influence of the plastic anisotropy on the collapse load. For some of the plate types tested new theoretical solutions have also been obtained. The models were 100 X 65, 100 x 100 and 100 x 135 cm plates 3,5 cm thick and were uniformly loaded by pressure. The investigations concerned five support conditions. For the 71 plates tested it has been found that the ratios of the values of the theoretical limit loads to those obtained by means of the yield line theory are contained within the limits 1,17 < qexp./qqteor. < 1,27. It follows that the kinematic approach in the limit analysis leads to safe loads as compared with the experimental ones. This conclusion is essential for the application of the yield line theory to practical problems.